A Nabataean funerary inscription from the Blaihed Museum. (May 2016) - Alzoubi, Mahdi; Smadi, Sahar
Abstract : This paper presents a study of an unpublished Nabataean funerary inscription from Dûmat al‐Jandal in Saudi Arabia. The inscription, in the Blaihed Museum private collection in al‐Jawf District in Saudi Arabia, is an important addition to the study of Nabataean funerary inscriptions, as it gives the first and only indication of the sale of a tomb, a practice that is considered abnormal for the Nabataeans. Parts of the inscription are missing or eroded. It is our hope that the publication of this article will lead to further research concerning the missing parts of the inscription.